Acute Angioedema Triggered by Daptomycin. Issue 2 (June 2016) - Gisler, Valentin; Müller, Sabine; Müller, Lionel; Jörg-Walther, Lukas; Sendi, Parham
Abstract Introduction Daptomycin is a cyclic lipopeptide antibiotic, frequently administered forStaphylococcus aureus bloodstream infections. Numerous studies have shown that daptomycin is relatively safe and well tolerated. Serious adverse events possibly related to this antimicrobial compound are rare. We report a case of acute angioedema triggered by daptomycin. Case Report A 60-year-old woman withS. aureus bacteremia without identified source was treated intravenously with high-dose beta-lactams at our institution. BecauseS. aureus bacteremia persisted on day 6, and in parallel, acute kidney injury developed, antimicrobial treatment was switched to a combination therapy with daptomycin and ceftriaxone. Shortly after completion of the first daptomycin administration, the patient developed lip and tongue swelling and dyspnea. Acute angioedema was clinically evident. Antibiotic therapy was switched to vancomycin, and the further clinical course was favorable. An intradermal test showed a significant wheal diameter for daptomycin, but negative results for ceftriaxone. Conclusion The association with daptomycin in this case is either probable or certain. Clinicians should be aware that daptomycin can cause immediate-type hypersensitivity reactions, including acute angioedema, even upon first administration.